Preparing Namibian Student Teachers to Teach Literacy in Mother Tongue - Alina Kakunde Niipare (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2019)
Scholars of language teaching agree that the development of initial literacy is best achieved when taught in the mother tongue. Namibia's language policy for schools prescribes teaching using mother tongue or the predominant local language as a medium of instruction during the first three years of schooling. This study reports on a study of how Namibian lecturers prepare student teachers to teach literacy in mother tongue (Oshikwanyama and Oshindonga) dialects of Oshiwambo language. Data were collected through classroom observations, semi-structured interviews and document analysis. Content analysis was used to analyse the data. The main findings are that most of the lecturers were proficient in the languages in question and they fluently explained the literacy content in Oshikwanyama and Oshindonga. However, the preparation was constrained by a lack of prescribed books in the African languages. The study aims at filling a gap in the literature on how Namibian student teachers are prepared to teach literacy in mother tongue grounded within a sociocultural perspective.